The Influence Of Regional Financial Performance On Economic Growth In Central Java Province - Komaedi Komaedi; Hadi Prabowo; Bahrullah Akbar; Dahyar Daraba; Muh. Ilham Muh. Ilham; Mansyur Mansyur; Ahmad Averus; Udaya Madjid (Eduvest - Journal of Universal Studies, 2024)
The phenomenon occurring in regional government administration, especially the large budgets in regional financial management, has not yet been able to drive economic growth. Central Java Province, which is one of the provinces with the largest regional budget (APBD) in Indonesia, experiences the same situation with economic growth that is not significantly better compared to other provinces in Indonesia. Therefore, the aim of this research is to analyze the extent of the influence of regional financial performance on economic growth in Central Java Province. This study employs a mixed-method approach, with quantitative research conducted initially followed by qualitative research across 35 regencies/cities in Central Java and the province itself. The results of this study indicate that the influence of regional financial performance on economic growth in Central Java during the period 2017-2022 was 0.021285 or 2.1285%, for the period 2017-2019 before the COVID-19 pandemic it was 0.021300 or 2.13%, and for the period 2020-2022 during the COVID-19 pandemic it was 0.089764 or 8.9764%.